ANALISIS EMPIRIS EFEKTIVITAS MEKANISME TRANSMISI KEBIJAKAN MONETER DI INDONESIA MELALUI JALUR NILAI TUKAR PERIODE 1990:2–2007:1 - Muh Natsir (Universitas Halu Oleo, 2017)
The aim of this research is to analyze the effectiveness of monetary policy transmission mechanism in Indonesia through exchange rate channel on period 1990:2-2007:1. This research use time series secondary data take from BI, BPS and IFS from many publications. Analysis technique that used was properties of Vector Auto Regression (VAR) model: Impulse Response Function (IRF) and Variance Decomposition (VD) The result of this research indicated that transmission mechanism of monetary policy through exchange rate channel work effectively with time lag about 16 quarterly. Exchange rates variable in this channel can be experience final target (inflations) about 19.69 % and interest rates differential about 43.36%. The result of this research is useful for Government and Bank of Indonesia to formulate and implementations the monetary policy effectively. This study result also can be used as reference for the researchers that want to hold further research.